Rheological impact of using cellulose nanocrystals (CNC) in cement pastes. (28th February 2020) - Montes, Francisco; Fu, Tengfei; Youngblood, Jeffrey P.; Weiss, Jason
Graphical abstract: Highlights: The influence of CNC on cement rheology was studied by measuring the changes in yield stress and viscosity. At low CNC dosages, cement pastes reduced yield stress by up to 54%. At high CNC dosages, cement pastes increased yield stress more than 10 times the original value. The presence of C3 A phase can significantly impact CNC rheological behavior. Abstract: The rheology of cement pastes containing cellulose nanocrystals (CNC) was assessed. Nine CNC obtained from various sources were added to cement pastes. Cement pastes were made using Type I/II and Type V cement with CNC addition rates from 0.023 vol% –3.311 vol%, relative to dry cement. Pastes were made using water to cement ratios of 0.30, 0.35, and 0.40. A Bingham model was used to evaluate changes in yield stress. The goal of these experiments was to identify the characteristics of the CNC which impact rheological behavior. The results showed the rheological behavior of cement pastes with CNC was not strongly related to Zeta potential, average CNC particle length, nor the average CNC particle respect ratio. However, it was found that maximum yield stress reduction occurred at higher CNC dosages as water to cement ratio increased. In addition, the rheological measurements suggested that at lower dosages (<0.2%), CNC behaved more like a water reducing admixture, reducing the yield stress up to 54%, while at higher dosage (more than 0.5%), CNC increased the paste yield stress, similar to certain viscosity modifying admixtures.